Implementasi Kepemimpinan Kepala Sekolah dalam Mewujudkan Program Sekolah Inklusi (Studi Kasus SDN 2 Nangewer Kabupaten Purwakarta) - Imam Syuhada; Darto Syahputra; Suharyanto Soro; Dinny Mardiana (Global Education Journal, 2025)
The implementation of inclusive schools is a strategic effort in realizing fair, quality, and friendly educational services for all students without discrimination. The success of the inclusion school program is largely determined by the principal's leadership in designing policies, managing resources, and building an inclusive school culture. This study aims to describe and analyze the implementation of the principal's leadership in realizing the inclusion school program at 2 Nangewer State Elementary School, Darangdan District, Purwakarta Regency. This study uses a case study approach with qualitative research methods. The data collection method was carried out through observation, in-depth interviews, and documentation studies involving school principals, teachers, education staff, parents, and other related parties. Data analysis techniques are carried out through the stages of data reduction, data presentation, and conclusion drawn, while data validity is tested through triangulation of sources and techniques. The results of the study show that (1) the leadership of the school principal has implemented through participatory inclusion program planning, teacher competency development, provision of supporting facilities and infrastructure, and the creation of an inclusive school climate and culture; (2) The principal plays the role of an educator, manager, motivator, and supervisor in encouraging the implementation of adaptive and friendly learning for students with special needs. However, the implementation of the inclusive school program still faces several obstacles, such as limited human resources, special support facilities, and uneven understanding of teachers. Therefore, it is necessary to strengthen policies, improve the competence of educators, and collaborate with various parties to optimize the implementation of inclusive schools.